Pitting corrosion OF Cr-Ni-Mo stainless steel in presence of MoO42- chloride solution - Zatkalíková, Viera; Markovičová, Lenka (Univerzita Pardubice, 2014)
The submitted manuscript focuses on the pitting corrosion of AISI 316Ti steel in very aggressive chloride solution with added sodium molybdate, which is considered the effective inhibitor of the local corrosion of stainless steels. The effect of molybdate on resistance of AISI 316Ti steel to pitting was tested in 5% ferric chloride solution by 24-hour exposition immersion tests. The tests were carried out at room temperature in the absence and presence of various molybdate concentrations (0.025 M, 0.05 M, 0.1 M molybdate). Resistance to pitting was evaluated on the bases of corrosion rates calculated from corrosion losses during immersion and by morphology of pitting, which was observed visually (character of pitting, pit shapes) and by optical microscope (pit shapes and pit profiles).